EJBM 2020
DOI: 10.7176/ejbm/12-1-05
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Culture as a Moderator Between Paternalistic Leadership Style and Organizational Commitment: A Case of Banking Sector, Pakistan

Abstract: This study seeks to examine the moderating role of organizational culture between Paternalistic Leadership Style and organizational commitment in the banking setting. This is an explanatory study based on 345 employees working in two private banks located in Lahore, Pakistan by using stratified sampling technique. Data were collected using the organizational commitment scale, paternalistic leadership scale and organizational culture scale. Descriptive statistics, reliability analysis, Pearson correlation were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…Asimismo Kalsoom et al (2020), quienes buscaron examinar el papel moderador de la cultura organizacional y el compromiso organizacional en el entorno bancario. La muestra estuvo dada 345 trabajadores que trabajan en dos bancos privados ubicados en Lahore, Pakistán.…”
Section: Marco Teóricounclassified
“…Asimismo Kalsoom et al (2020), quienes buscaron examinar el papel moderador de la cultura organizacional y el compromiso organizacional en el entorno bancario. La muestra estuvo dada 345 trabajadores que trabajan en dos bancos privados ubicados en Lahore, Pakistán.…”
Section: Marco Teóricounclassified
“…In developing countries like Pakistan, It is also observed that leadership is influenced mainly by culture (Zahid et al, 2019). The projections of individuals or subordinates create pressure by anticipating too high and turn them into a paternalistic leader (Kalsoom et al, 2020). Leaders face socio-cultural pressures which makes it more turbulent for them to act in a more professional manner (Soon & Wee, 2013).…”
Section: Integrals Of Emotional Intelligencementioning
confidence: 99%